Racial and ethnic inequality in employer provided fringe benefits - Wallace Mok; Zahra Siddique (Institute for the Study of Labor (IZA), 2011)
We examine racial and ethnic inequality in offers of employer provided fringe benefits (health insurance, life insurance and pension). Restricting to full-time workers in the private sector, we find that African Americans are significantly less likely to get fringe benefit offers than non-Hispanic whites after we control for individual differences in age and youth characteristics that matter for labor market success using the 1979 cohort of the National Longitudinal Survey of Youth. We do not find ethnic differences in the 1979 cohort or racial/ethnic differences in the 1997 cohort to be significantly large after controlling for individual differences in age and youth characteristics. Irrespective of race, ethnicity, gender or cohort, we always find that older workers are more likely to get fringe benefit offers as are workers with higher cognitive ability and years of education at age 22. We find that the cross-sections from the 1979 cohort of the National Longitudinal Survey of Youth have more fringe benefit offers than cross-sections from the 1997 cohort. A large part of the difference across cohorts can be explained by the older age profile of cross-sections from the 1979 cohort. Some part of the difference across cohorts can also be explained by differences in family background characteristics, particularly changing family structures which are important for non-Hispanic whites and for African American men. Improvements in cognitive ability and years of education at age 22 for the 1997 cohort increase the unexplained difference in fringe benefit offers across the two cohorts for women (irrespective of race or ethnicity), but not for men.
urn:nbn:de:101:1-201203016314
Keywords: I11; J15; J32; 330; economics of minorities and races; non-wage labor costs and benefits; Betriebliche Sozialleistungen; Arbeitsmarktdiskriminierung; Ethnische Diskriminierung; Farbige Bevölkerung; Weiße; USA